A Stochastic Characterization of Hydrogen Peroxide-Induced Regulated Cell Death in Microcystis aeruginosa - Giannuzzi, Leda; Lombardo, Tomás; Juárez, Iván; Aguilera, Anabella; Blanco, Guillermo (Frontiers in Microbiology, 2021)
Regulated cell death (RCD) encompasses the activation of cellular pathways that initiate and execute a self-dismissal process. RCD occur over a range of stressors doses that overcome pro-survival cellular pathways, while higher doses cause excessive damage leading to passive accidental cell death. Hydrogen peroxide (HP) has been proposed as a potential tool to control harmful cyanobacterial blooms, given its capacity to remove cyanobacterial cells and oxidize cyanotoxins. HP is a source of hydroxyl radicals and is expected to induce RCD only within a limited range of concentrations. This property makes this compound very useful to better understand stress-driven RCD. In this work, we analyzed cell death in microcystin-producing Microcystis aeruginosa by means of a stochastic dose response model using a wide range of HP concentrations (0, 0.29, 1.76, 3.67, 7.35, 14.70 and 29.5mM). We used flow cytometry and unsupervised classification to study cell viability and characterize transitional cell death phenotypes after exposing cells to HP for 48 and 72 h. Non-linear regression was used to fit experimental data to a logistic cumulative distribution function (cdf) and calculate the half maximal effective concentration (EC50). The EC50 of M. aeruginosa exposed to HP were 3.77 ± 0.26 mM and 4.26 ± 0.22 mM at 48h and 72h, respectively. The derivative of cdf (probability density function; pdf) provided theoretical and practical demonstration that EC50 is the minimal dose required to cause RCD in 50% of cells, therefore maximizing the probability of RCD occurrence. 1.76 mM HP lead to an antioxidant stress response characterized by increased reactive oxygen species levels and HP decomposition activity. The exposure of 3.67 mM HP induced a dose-related transition in cell death phenotype, and produced several morphological changes (a less dense stroma, distortion of the cell membrane, partial disintegration of thylakoids, extensive cytoplasmic vacuolation and highly condensed chromatin). The EC50 and the stochastic cdf and pdf together with the multidimensional transitional phenotypic analysis of single cells contribute to further characterize cell death pathways in cyanobacteria.